Pengaruh Penerapan Good Corporate Governance Terhadap Kinerja Keuangan Studi Empiris Pada Perusahaan Perbankan yang Terdaftar Di BEI Tahun 2010-2014) - Putri, Diana Surya Kusuma, Drs. Wiyadi, MM, Ph.D (2016)
This study aims to determine and analyze the effect of the implementation of good corporate governance on financial performance in the banking companies listed in Indonesia Stock Exchange (BEI) in 2010-2014, either partially or simultaneously. The indicators used to describe good corporate governance in this study consisted of the size of the board of directors, the size of the board of commissioners, the proportion of independent directors, audit committees, and institutional ownership. The analytical method used in this research is descriptive statistics and multiple linear regression, in accordance with the purpose of research is to analyze the influence of independent variables on the dependent variable. The sample used in this study are all banking companies listed on the Stock Exchange Indonesia (BEI) 2010-2014. Determination of the sample using purposive sampling method. By using this method obtained 76 data sampled for analysis. Results of testing the hypothesis in this study, suggesting that the size of the board of directors has a significant positive effect on financial performance. The proportion of independent directors has a significant positive effect on financial performance. Institutional ownership has a significant positive effect on financial performance. The size of the board of commissioners has a significant negative effect on financial performance. The audit committee has a significant negative effect on financial performance.